Vaccination against influenza among Lebanese health care workers in the era of coronavirus disease 2019 - Dalal Youssef; Atika Berry; Janet Youssef; Linda Abou-Abbas (BMC, 2022)
Abstract Background Health-care workers (HCWs) are at a higher occupational risk of contracting and transmitting influenza. Annual vaccination is an essential tool to prevent seasonal influenza infection. However, HCWs vaccine hesitancy remains a leading global health threat. This study aims to evaluate the flu vaccination coverage rates among Lebanese HCWs and to assess their knowledge, attitudes, practices, perceived barriers, and benefits toward the flu vaccine during the COVID-19 pandemic. In addition, we sought to identify the factors associated with flu vaccine uptake. Methods A cross-sectional study using an online survey was conducted in Lebanon among HCWs between 14 and 28 October 2020. Multivariable logistic regression was carried out to identify the factors associated with influenza vaccine uptake. Results A total of 560 HCWs participated in the survey of whom 72.9% were females, and 53.9% were aged between 30-49 years. Regarding Flu vaccination uptake, the rate has risen from 32.1% in 2019-2020 to 80.2% in 2020-2021 flu season. The majority of HCWs had a good knowledge level and a positive attitude toward flu vaccination. Regarding their practices, less than 50% of HCW were currently promoting the importance of getting the flu vaccine. The majority (83.3%) ranked the availability of a sufficient quantity of vaccines as the most significant barrier to flu vaccination. The main perceived flu vaccination benefits were enhancing patient safety, minimizing the viral reservoir in the population, decreasing hospital admission, and avoiding influenza and COVID-19 co-infection. The odds of influenza vaccine uptake was lower in unmarried compared to married HCWs (OR = 0.527, CI (0.284-0.978). However, HCWs having received the influenza vaccine in the previous season (OR = 6.812, CI (3.045-15.239)), those with good knowledge level (OR = 3.305, CI (1.155-9.457)), low perceived barriers (OR = 4.130, CI (1.827-9.334)) and high perceived level of the benefits (OR = 6.264, CI (2.919-13.442)) of the flu vaccination were found more prone to get the flu vaccine. Conclusion Flu vaccination uptake has increased among HCWs during the 2020-2021 flu season compared with the previous one. Continuing education as well as ensuring free, equitable, and convenient access to vaccination are still required to increase the annual flu vaccination uptake among HCWs.